MSME branding training for coastal communities - Rizki Martadinata; Fajar Rahmat Sidik; Akbar Raihanza; Miskatul Lathifah; Anggun Nabira; Nadia Nursamala; Sabrina Sabrina; Mutiara Safelia; Siti Syahriwulan; Dinda Rahmalia; Iful Rahmawati Mega (Community Empowerment, 2024)
Coastal areas not only serve as the economic hub for local communities engaged in fishing but also for Micro, Small, and Medium Enterprises (MSMEs). Due to their geographic proximity to the sea, coastal communities involved in MSMEs face some challenges in marketing their products, thus limiting their market reach. One of the hurdles experienced by coastal communities is a lack of understanding of technology usage in digital marketing. The objective of this community service is to educate MSMEs in coastal areas about product branding. The method employed involves providing training sessions. By the end of the program, MSME operators will have designed logos for their products and can begin transitioning to online sales.